Development of Hybrid Polymeric Polyerthersulfone (PES) Membrane Incorporated with Powdered Activated Carbon (PAC) for Palm Oil Mill Effluent (POME) Treatment - Ling Yong, wong; Ng, Choon Aun; Bashir, Mohammed J K; Ng, Seng Lai (International Journal of Integrated Engineering, 2018)
The development of water treatment system to produce low cost & high quality effluent has become extremely important nowadays. Since year 1960, membrane technology has transformed from laboratory stage to industrial applications stage. The development of newer membrane modules in recent years helps the membrane industry growth rapidly, but the technology is still not so universal due to membrane fouling issue. Additional of PAC directly into the treatment system has proven to be a promising strategy to reduce membrane fouling and improve efficiency of the system. However, there are also drawbacks caused by excessive PAC within a treatment system. In this study, the potential of integrating the PAC into PES membrane was evaluated and its performance was assessed. The result shows that the PAC integrated membrane has higher permeation rate, which is 231 L/m2.hr compare to the one without PAC integrated membrane, which only has 89 L/m2.hr. In addition, PAC integrated membrane was able to achieve up to 81% and 67% removal rate, compared to the one without PAC integrated which only can remove 10% and 35% of COD and color respectively. Besides, the structural property of the membranes was observed using scanning electron microscopy (SEM). The results showed a trend where the membrane with higher concentration of PAC integrated will have better performance in both pollutant removal ability as well as the membrane fouling control.